Dielectric barrier discharge-accelerated one-pot synthesis of sulfur quantum dots for fluorescent sensing of lead ions and l-cysteine. Issue 62 (11th July 2022) - Yang, Manlin; Li, Chenghui; Tian, Yunfei; Wu, Lan; Hu, Jing; Hou, Xiandeng
Abstract : One-pot facile synthesis of sulfur quantum dots using a dielectric barrier discharge (DBD)-accelerated H2 O2 etching strategy in 20 min for the detection of Pb 2+ ions and l -cysteine. Abstract : Here, we report a novel method for the one-pot facile synthesis of sulfur quantum dots (SQDs) based on a dielectric barrier discharge (DBD)-accelerated H2 O2 etching strategy within merely 20 min. The formation mechanism of SQDs was investigated, with which an "ON–OFF–ON" fluorescence sensor was developed for the detection of Pb 2+ ions and l -cysteine.